Meningkatkan Motivasi Belajar Peserta Didik Di SMKN 6 Kota Serang Untuk Mempersiapkan SDM Unggul Menyongsong Indonesia Emas 2045 - Ramah Maysarani; Putri Anggraeni; Mohamad Saeful Anwar; Latif Latif; Yanto Nius Gulo (Lembaga Pengembangan Kinerja Dosen, 2024)
Learning motivation plays a significant role for students. This motivation increases students’ interest in completing learning activities. When students are motivated by their environment and themselves, their learning outcomes also improve. The methods used in community service activities (PKM) are influenced by various factors, such as monotonous teaching methods, lack of teacher support, and the influence of technology. PKM uses interactive lecture methods that utilize media, discussions, and Q&A sessions to increase students’ learning motivation. This highlights the importance of motivation to support oneself in achieving goals and becoming a better individual. This community service aims to increase the learning motivation of students at SMKN 6 Serang cities, as motivation is one of the factors that influence students’ success. When someone is motivated to learn, they will achieve the desired learning outcomes. Motivation acts as a driving force to achieve good results. People engage in activities because they have motives. High learning motivation will yield optimal results. This activity aims to prepare students as participants who, based on their respective skills, can face challenges in starting their careers.